Ammonia stress corrosion cracking acceleration test method

An accelerated ammonia SCC test method using ammonium carbamate and controlled potential polarization in liquid ammonia effectively promotes pitting corrosion, enabling accurate and rapid evaluation of metal materials' resistance to stress corrosion cracking.

JP2024179322AActive Publication Date: 2024-12-26JFE STEEL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023098072
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-26
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

Existing ammonia stress corrosion cracking (SCC) evaluation methods are inaccurate and require long periods due to dominance of general corrosion over pitting corrosion, making it difficult to assess the susceptibility of metal materials in a liquid ammonia environment.

Method used

An accelerated test method involving the use of ammonium carbamate and controlled potential polarization in liquid ammonia, promoting pitting corrosion by destabilizing the oxide film on the metal surface, thereby evaluating ammonia SCC susceptibility in a short period.

Benefits of technology

The method accurately evaluates ammonia SCC susceptibility of metal materials in a short time, allowing for precise assessment of their resistance to stress corrosion cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024179322000001
    Figure 2024179322000001
  • Figure 2024179322000002
    Figure 2024179322000002
Patent Text Reader

Abstract

To provide an ammonia stress corrosion cracking acceleration test method capable of evaluating ammonia stress corrosion cracking sensitivity of a metal material with excellent accuracy in a short period.SOLUTION: In an ammonia stress corrosion cracking acceleration test method, a metal test piece to which external stress is added or which has residual stress is immersed in ammonium carbamate of 0.01 mass% or more and liquid ammonia containing O2 of 0.002 to 0.200 bar at a gas partial pressure, and is polarized to 0 to +1.0 V relative to corrosion potential.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for accelerated ammonia stress corrosion cracking testing of metal materials such as tanks used in a liquid ammonia environment. [Background technology]

[0002] In recent years, liquid ammonia has been known to emit CO when burned. 2 Since it does not emit any CO2, it has been attracting attention as a clean energy source, and large-scale demand is expected. This has led to a demand for larger facilities to transport and store liquid ammonia. In general, when making tanks larger, thinner steel is used to reduce weight and construction costs, and therefore the use of high-strength steel is desirable.

[0003] On the other hand, in a liquid ammonia environment, there is concern that carbon steel may suffer from stress corrosion cracking due to liquid ammonia (hereinafter referred to as ammonia SCC). Therefore, for carbon steel structures that handle liquid ammonia, such as piping, storage tanks, tank cars, and line pipes, steel materials with low ammonia SCC susceptibility have been used and operational measures have been taken to suppress ammonia SCC.

[0004] SCC is a phenomenon that leads to destruction due to the superposition of corrosion reactions and stress, and occurs when material factors, environmental factors, and stress factors meet certain conditions. For example, ammonia SCC is known to correlate with the strength and hardness of a material. In other words, it is known that the higher the strength and hardness, the more ammonia SCC occurs, and when using carbon steel, it is considered desirable to use materials with a tensile strength of less than 600 MPa.

[0005] Therefore, when applying new materials that have both high strength and excellent ammonia SCC resistance, it is necessary to accurately evaluate the ammonia SCC susceptibility.On the other hand, since evaluating ammonia SCC susceptibility by exposure testing in an actual liquid ammonia tank requires long-term testing, an accelerated test that can evaluate the ammonia SCC susceptibility of steel in a short period of time is desired.

[0006] Such accelerated tests using liquid ammonia are disclosed in Patent Document 1 and Non-Patent Document 1. 2 and saturated CO 2 This paper describes a test method for evaluating ammonia SCC susceptibility in a short period of time by accelerating iron dissolution through anodic polarization of test steel pieces in liquid ammonia containing ammonium nitrate. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 60-10575 [Non-patent literature]

[0008] [Non-Patent Document 1] Yoichi Nakai, "Development of an accelerated test method for stress corrosion cracking in liquid ammonia", Iron and Steel, Vol. 67, No. 14, 1981, pp. 2226-2233 Summary of the Invention [Problem to be solved by the invention]

[0009] In the test methods described in Patent Document 1 and Non-Patent Document 1, the test pieces are anodically polarized at +2V vs Pt, but excessive anodic polarization causes general corrosion to dominate, and pitting corrosion (localized corrosion), which is the starting point of ammonia SCC, does not occur sufficiently, making it difficult to say that ammonia SCC susceptibility is accurately evaluated. In addition, since the occurrence of pitting corrosion (localized corrosion) is not promoted, long-term testing is required for materials that are not highly susceptible to ammonia SCC.

[0010] The present invention aims to solve the above problems and provide an accelerated ammonia SCC test method that can evaluate the ammonia SCC susceptibility of metal materials used in tanks for transporting and storing liquid ammonia with high accuracy and in a short period of time. [Means for solving the problem]

[0011] In order to achieve the above object, the present inventors conducted a detailed study on the ammonia SCC mechanism of steel sheet in liquid ammonia and obtained the following findings.

[0012] In a liquid ammonia environment, the following corrosion reactions occur on steel plates: Anode reaction: Fe → Fe 2+ +2e - Cathodic reaction: O 2 +2NH 4 + +4e - →2OH - +2NH 3

[0013] As a result of the above corrosion reaction, an inactive oxide film is formed on the steel sheet surface, but pitting corrosion occurs when the oxide film dissolves locally in unstable areas. The pits become stress-concentrating areas, and film destruction and corrosion reactions progress at the tip of the pit, eventually leading to fracture. Therefore, we came up with the idea of ​​destabilizing the oxide film that forms on the steel sheet surface in order to promote the initiation of pitting corrosion, which is the starting point of ammonia SCC.

[0014] The inventors then discovered that by holding the steel sheet at a specific potential in liquid ammonia, the oxide film on the surface of the steel sheet becomes unstable, making it possible to evaluate the ammonia SCC susceptibility in a short period of time, which led to the completion of the present invention.

[0015] The present invention has been made based on the above findings, and the gist of the present invention is as follows.

[0016] [1] Metal specimens to which external stress has been applied or which have residual stress are subjected to a gas partial pressure of 0.002 to 0.200 bar containing 0.01 mass% or more ammonium carbamate. 2 and polarizing the specimen to a corrosion potential of 0 to +1.0 V.

[0017] [2] The accelerated ammonia stress corrosion cracking test method according to [1], wherein the surface of the metal test piece immersed in the liquid ammonia is cathodically polarized and then polarized to 0 to +1.0 V with respect to a corrosion potential.

[0018] [3] The accelerated ammonia stress corrosion cracking test method according to [1] or [2], wherein the liquid ammonia is stirred during the test.

[0019] [4] Metal specimens to which external stress has been applied or which have residual stress are subjected to a thermal shock test in a gas atmosphere containing 0.05 to 0.50 mass% ammonium carbamate and a partial pressure of 0.002 to 0.200 bar O. 2 1. A method for accelerated ammonia stress corrosion cracking testing, comprising: immersing a specimen in liquid ammonia containing

[0020] [5] The accelerated ammonia stress corrosion cracking test method according to [4], wherein the surface of the metal test piece immersed in the liquid ammonia is cathodically polarized.

[0021] [6] The accelerated ammonia stress corrosion cracking test method according to [4] or [5] above, wherein the liquid ammonia is stirred during the test. Effect of the Invention

[0022] According to the accelerated ammonia stress corrosion cracking test method of the present invention, it is possible to evaluate the ammonia SCC susceptibility of metal materials applied to tanks and the like used in a liquid ammonia environment with good accuracy and in a short period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as the present embodiment) will be described in detail. The present invention is not limited to the following embodiment, and can be modified in various ways within the scope of the present invention. In the embodiment of the present invention, A (numerical value) to B (numerical value) means A or more and B or less.

[0024] [Polarized from 0 to +1.0 V relative to the corrosion potential] In one embodiment of the test method of the present invention, a metal test piece to which an external stress has been applied or which has residual stress is subjected to a gas partial pressure of 0.002 to 0.200 bar containing 0.01 mass% or more ammonium carbamate. 2 The specimen is immersed in liquid ammonia containing 1.0 V and polarized to 0 to +1.0 V with respect to the corrosion potential.

[0025] By polarizing the metal test piece to 0 to +1.0 V with respect to the corrosion potential, the oxide film formed on the surface of the metal test piece by immersion in liquid ammonia becomes unstable. On the surface of a metal test piece to which external stress has been applied or which has residual stress, pitting corrosion due to local corrosion is promoted, and the ammonia SCC susceptibility can be evaluated in a short period of time. On the other hand, when the metal test piece is polarized (cathodic polarization) to less than 0 V with respect to the corrosion potential, the cathodic reaction is promoted on the surface of the metal test piece, making it difficult to evaluate the ammonia SCC susceptibility of the metal test piece. In addition, when the metal test piece is polarized to more than +1.0 V with respect to the corrosion potential, general corrosion is promoted on the surface of the test piece compared to local corrosion, which is the starting point of ammonia SCC, and there is a risk that the ammonia SCC susceptibility cannot be evaluated in a short period of time. Furthermore, when general corrosion becomes dominant, local corrosion, which is the starting point of SCC, does not occur, and there is a risk that the ammonia SCC susceptibility itself cannot be evaluated. For this reason, it is specified to polarize the metal test piece to 0 to +1.0 V with respect to the corrosion potential. The applied potential relative to the corrosion potential is preferably +0.2 V or more, more preferably +0.4 V or more, and is preferably +0.8 V or less, more preferably +0.6 V or less.

[0026] The corrosion potential is the potential measured by immersing a metal test piece for which ammonia SCC susceptibility is to be evaluated, or a metal test piece taken from the same material as the metal material to be evaluated, in liquid ammonia for 5 minutes or more while applying external stress or while maintaining residual stress. The method for measuring the potential is not particularly limited, but it can be measured by the two-electrode method or the three-electrode method.

[0027] The polarization (application of electric potential) and the measurement of the corrosion potential of the metal test piece can be performed, for example, by using a potentiostat (a constant potential electrolysis device) with the metal test piece as the working electrode (sample electrode). In this case, it is preferable to use platinum (Pt) electrodes, which are stable in liquid ammonia, as the counter electrode and reference electrode.

[0028] <Test solution> In the test method of the present invention, 0.01 mass% or more of ammonium carbamate and O with a gas partial pressure of 0.002 to 0.200 bar are used.2 Liquid ammonia containing is used as the test solution.

[0029] [Ammonium carbamate content: 0.01 mass% or more] Liquid ammonia usually contains trace amounts of CO as an impurity. 2 is present, and CO 2 dissociates and reaches an equilibrium state as shown in the following reaction equation. 2NH 3 +CO 2 ⇔NH 4 CO 2 NH 2 ⇔NH 4 + +NH 2 CO 2 -

[0030] The electrical conductivity of pure liquid ammonia is small, but that of ammonium carbamate (NH 4 CO 2 NH 2 ), the dissociation reaction increases the electrical conductivity of the liquid ammonia, accelerating the corrosion reaction. If the ammonium carbamate content in the liquid ammonia is less than 0.01 mass%, such an effect cannot be obtained, and it is difficult to accelerate ammonia SCC by polarizing the metal test piece. Therefore, the ammonium carbamate content in the liquid ammonia is specified to be 0.01 mass% or more. It is preferably 0.03 mass% or more, more preferably 0.10 mass% or more, and even more preferably 0.30 mass% or more. The upper limit of the ammonium carbamate content in the liquid ammonia is not particularly limited, and it may be contained up to the saturation amount. For example, it may be 6.00 mass% or less, 1.00 mass% or less, or 0.50 mass% or less.

[0031] [Ammonium carbamate content: 0.05-0.50 mass%] In another embodiment of the test method of the present invention, a metal test piece to which an external stress has been applied or which has residual stress is subjected to a gas partial pressure of 0.002 to 0.200 bar containing 0.05 to 0.50 mass% ammonium carbamate. 2 It is sufficient to simply immerse the metal test piece in liquid ammonia containing the above-mentioned compound, and the potential applied to the metal test piece can be set to 0 V, i.e., it is not necessary to polarize the metal test piece.

[0032] Ammonium carbamate is converted to carbamate ion (CO 2 NH 2 - ) is formed. The carbamate ions have the effect of destroying the inactive oxide film on the surface of the metal test piece, so by optimizing the content of the carbamate ions, the oxide film can be destabilized without causing the anodic polarization, and ammonia SCC can be promoted. If the content of ammonium carbamate in liquid ammonia is less than 0.05 mass%, the rate of oxide film regeneration by corrosion reaction is significantly higher than the rate of oxide film destruction by carbamate ions, so the effect cannot be obtained. On the other hand, if the content of ammonium carbamate in liquid ammonia is more than 0.50 mass%, the rate of oxide film destruction by carbamate ions is high, and the corrosion form is close to general corrosion rather than pitting corrosion (local corrosion), so the effect cannot be obtained. Therefore, if anodic polarization is not performed, the content of ammonium carbamate in liquid ammonia is specified to be 0.05 to 0.50 mass%. It is preferably 0.10 mass% or more, more preferably 0.15 mass% or more, even more preferably 0.20 mass% or more, and is preferably 0.45 mass% or less, more preferably 0.40 mass% or less, even more preferably 0.35 mass% or less.

[0033] Note that, when the content of ammonium carbamate in liquid ammonia is 0.05 to 0.50 mass %, an embodiment in which polarization is performed from more than 0 V to +1.0 V or less with respect to the corrosion potential is also included within the scope of the test method of the present invention.

[0034] The method of adding ammonium carbamate to liquid ammonia is not particularly limited, but it is preferable to place a predetermined amount of ammonium carbamate in the test vessel before introducing liquid ammonia. The ammonium carbamate is placed in the test vessel in an amount of CO 2 that can obtain the predetermined amount of ammonium carbamate. 2 Gas injection or solid CO 2 This can be substituted with dry ice.

[0035] [O 2 Content: 0.002 to 0.200 bar at gas partial pressure O 2 Since O has the ability to form an oxide film in liquid ammonia, it was used in the evaluation of ammonia SCC susceptibility. 2 The presence of O in liquid ammonia is essential. 2 If the content is less than 0.002 bar in terms of gas partial pressure, such an effect cannot be obtained, making ammonia SCC evaluation difficult. 2 If the content exceeds 0.200 bar in terms of gas partial pressure, the rate of oxide film formation increases significantly, the oxide film becomes stable, and pitting corrosion does not occur, making ammonia SCC evaluation difficult. 2 The content is specified to be 0.002 to 0.200 bar in terms of gas partial pressure, preferably 0.005 bar or more, more preferably 0.020 bar or more, and preferably 0.175 bar or less, more preferably 0.150 bar or less.

[0036] O to liquid ammonia 2 The method of adding is not particularly limited, but 2 From the viewpoint of stable supply of O, a specified amount of O was added to the test vessel before introducing liquid ammonia. 2 It is preferable to blow in a gas. 2 The gas is blown in at the predetermined amount of O 2 This can be substituted by blowing in an amount of air gas that will provide the gas partial pressure.

[0037] [Liquid ammonia] The purity of the liquid ammonia used in the test solution is not particularly limited, but H 2 When liquid ammonia contains H, it is easy to suppress stress corrosion cracking of metal test pieces. 2 The content of O and oil is preferably less than 0.05 mass% each.

[0038] [Cathode polarization] A passive film may be formed on the surface of the metal test piece before it is immersed in liquid ammonia. By performing cathodic polarization immediately after immersion in liquid ammonia, the passive film on the surface of the metal test piece can be removed, the initial surface state can be homogenized, and the effect of the subsequent anodic polarization can be enhanced, enabling a more accurate ammonia SCC susceptibility evaluation. The conditions for cathodic polarization are not particularly limited, but it is preferable to perform the cathodic polarization at -1.0V or less and -3.0V or more with respect to the corrosion potential, for 5 minutes to 30 minutes.

[0039] [Liquid ammonia stirred during testing] The corrosion reaction is affected by the composition of the liquid ammonia solution on the metal specimen surface. 2 By stirring the liquid ammonia containing O, the solution composition on the surface of the immersed metal test piece can be made uniform, enabling a more accurate ammonia SCC susceptibility evaluation. Furthermore, stirring promotes the supply of ions to the metal test piece surface, shortening the time required for ammonia SCC susceptibility evaluation. Therefore, the ammonium carbamate and O during the test 2 It is preferable to stir the liquid ammonia containing the above. Since the ammonia SCC susceptibility is affected by nitrogen, carbon dioxide, oxygen, etc., it is preferable to perform stirring using a stirrer. In order to stabilize the supply of ions to the metal test piece surface, it is preferable to perform stirring continuously at 10 rpm or more.

[0040] <Metal test piece> The test method of the present invention is a method for promoting ammonia SCC by applying an electric potential, and therefore can be applied to conductive metal materials. The metal materials are not particularly limited in terms of their component composition or metal structure. Specific examples of the metal materials include those containing metal elements (e.g., Fe, Cu, Al, Ni, Ti, etc.) as the main component (i.e., 50 mass% or more), such as steel (iron alloy), copper alloy, aluminum alloy, nickel alloy, titanium alloy, etc. In particular, since these materials are generally used in structures exposed to a liquid ammonia environment and resistance to ammonia SCC is important, it is preferable to apply the method to steel materials.

[0041] When a steel material is used as the metal test piece, the carbon equivalent and hardness of the steel material are not particularly limited. It is generally known that the higher the carbon equivalent and hardness of a steel material, the higher the ammonia SCC susceptibility, and it is preferable that the steel test piece has a carbon equivalent of 0.05% or more and a Vickers hardness of 100 Hv or more. The metal test piece used in the test method of the present invention may be one taken from a metal material whose ammonia SCC susceptibility is to be evaluated, or one taken from a metal material having the same or similar component composition and metal structure as the said metal material.

[0042] The shape and size of the metal test piece are not particularly limited and may be appropriately determined depending on the test cell and the method of applying external stress to be used or may be selected from known standards. However, the exposed area (cm2) of the metal test piece may be adjusted so as to reduce the effect of the corrosion reaction on the solution composition. 2 The specific liquid volume, which is the amount of liquid ammonia solution (mL) relative to the 2 The upper limit of the specific liquid volume is not particularly limited, but if the specific liquid volume is excessively large, the cost of the test equipment etc. will increase, so it is preferable that the upper limit is 500 mL / cm 2 It is preferable that:

[0043] [External stress / residual stress] Since the test method of the present invention is an accelerated ammonia stress corrosion cracking test, a metal test piece to which an external stress has been applied or which has a residual stress is immersed in a test solution. The method of applying the external stress or the residual stress is not particularly limited, but for example, an external stress can be applied by a known method such as four-point bending, U-bending, or a constant load method, and a residual stress can be applied by carrying out a heat treatment, welding, processing, or the like.

[0044] The magnitude of the applied external stress or residual stress may be appropriately set depending on the test purpose (for example, the intended use of the material to be evaluated), but it is preferable to load 20% or more of the yield strength YS (MPa) of each metal test piece. Since ammonia SCC can be promoted as the applied external stress or residual stress is increased, there is no particular upper limit as long as damage such as cracks is not caused to the metal test piece itself.

[0045] <Other test conditions> The test temperature (temperature of the test solution) at which the test method of the present invention is carried out can be appropriately selected depending on the purpose of the test, but since the corrosion reaction is suppressed at low temperatures and the test period tends to be long, it is preferably set to 0 to 60° C. In order to further improve the test accuracy, it is preferable to set the error between the set test temperature and the actual test temperature within ±5° C.

[0046] The test period for carrying out the test method of the present invention is not particularly limited and can be set appropriately depending on the intended use of the metallic material to be evaluated, but in order to apply a new material, the shorter the test period, the better, and it is preferably within 720 hours. Since an ammonia SCC test under an actual tank environment (actual liquid ammonia) generally requires a test period of about one year, the use of the test method of the present invention can shorten the test period to about 1 / 10 or less.

[0047] The test conditions other than those mentioned above are not particularly limited, and may be appropriately selected from known conditions used in corrosion tests. Test equipment, test cells, and the like may be those known in the art, such as those described in Patent Document 1 and Non-Patent Document 1. EXAMPLES

[0048] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.

[0049] [Ammonia SCC occurrence in actual tank environment] As a preliminary study to confirm the effectiveness of the test method of the present invention, seven types of steel (steel types A to G) with different composition were used as test steels, and an ammonia SCC test was performed in an actual tank environment using actual liquid ammonia to evaluate the ammonia SCC susceptibility.

[0050] Table 1 shows the carbon equivalent (CE), yield strength (YS) and Vickers hardness (HV0.5) of the steel materials A to G subjected to the ammonia SCC test.

[0051] The carbon equivalent (CE) was calculated from the composition of the test steel material using the following formula. CE=C+Mn / 6+Si / 24+Ni / 40+Cr / 5+Mo / 4+V / 14 (In the formula, the element symbols indicate the content (mass%) of each element in the test steel material.)

[0052] The yield strength and Vickers hardness were measured at the 1 / 4 position of the plate thickness in accordance with JIS Z 2241 and JIS Z 2244. The Vickers hardness was measured at 20 points using a Vickers test with a load of 500 g, and the average value was calculated.

[0053] Test pieces measuring 5 mm thick x 15 mm wide x 115 mm long were taken from the 1 / 4 plate thickness position of the test steels A to G. The taken test pieces were ultrasonically degreased in acetone for 5 minutes, and then an external stress (100% YS) equal to the yield strength of each test piece was applied by four-point bending. The four-point bent test pieces were immersed in a real liquid ammonia tank and removed after one year. After removing the corrosion products from the surface of the removed test pieces, the surface and cross section of the test pieces were visually observed for cracks and the presence or absence of cracks was evaluated.

[0054] Those where cracks occurred were rated as SCC occurrence "Good", those where pitting corrosion occurred but not cracks were rated as pitting corrosion occurrence "△", and those where neither cracks nor pitting corrosion occurred were rated as no SCC "X". The results are shown in Table 1 as the SCC occurrence status in an actual liquid ammonia tank.

[0055] [Table 1]

[0056] As can be seen from Table 1, in the actual liquid ammonia tank, neither SCC nor pitting corrosion, which is the initiation point of SCC, occurred in steels A and B. Steel C did not develop SCC, but pitting corrosion occurred. Steels D to G developed SCC.

[0057] [Ammonia SCC accelerated test] The ammonia SCC acceleration test of the present invention was carried out on the test steels A to G for which the ammonia SCC occurrence state in an actual tank environment was examined as described above, and the ammonia SCC susceptibility was evaluated.

[0058] Table 2 shows the test conditions for the ammonia SCC accelerated test. Test pieces measuring 5 mm thick x 15 mm wide x 115 mm long were taken from the 1 / 4 position of the plate thickness of the test steels A to G. They were ultrasonically degreased in acetone for 5 minutes, and an external stress (100% YS) equal to the yield strength of each test piece was applied by four-point bending. Ammonium carbamate and O were added to the test cell in which the four-point bending test pieces were placed. 2 was introduced to the specified amount shown in Table 2, and then 2 L of liquid ammonia was filled. The specific liquid volume was 42 mL / cm 2 After that, the corrosion potential of the test piece was measured by a potentiostat, and the test was started by controlling the corrosion potential after 1 hour to a predetermined potential. After 168 to 2160 hours of immersion, the corrosion products on the surface of the test piece were removed, and the surface and cross section were visually observed for cracks to evaluate the presence or absence of cracks.

[0059] In the immersion test, liquid ammonia with a purity of 99.999% or more was used. Measurement of potential and application of potential using a potentiostat were performed by the three-electrode method, and platinum electrodes were used as the reference electrode and counter electrode. The test temperature was set at 25°C. Stirring during the test was performed continuously at 10 rpm using a stirrer placed in the test cell.

[0060] The occurrence of SCC was evaluated by conducting such an immersion test 10 times for each test number, and those that had one or more cracks throughout the test were judged as having SCC occurrence (good), those that had no cracks but had one or more pitting corrosion (good), and those that had neither SCC nor pitting corrosion (bad). For those that showed a result of SCC occurrence (good) or pitting corrosion occurrence (good), the probability of SCC or pitting corrosion occurrence was calculated.

[0061] For those that did not have SCC or pitting corrosion, the evaluation accuracy was judged to be "good" if the SCC occurrence status in the actual liquid ammonia tank for the same steel type was the same as "X" in Table 1. For those that had SCC or pitting corrosion, the evaluation accuracy was judged to be "good" if the SCC occurrence status in the actual liquid ammonia tank for the same steel type was the same ("O" or "△") in Table 1 and the occurrence probability was 70% or more. The occurrence probability is shown as a percentage of the number of tests in which the occurrence status was confirmed out of 10 immersion tests. In addition, in tests in which the evaluation accuracy was judged to be good, those with a test period of 720 hours or less were judged to have a "good" evaluation period. Those other than those judged to be "good" in terms of evaluation accuracy and evaluation period were judged to be "bad". Table 2 shows the SCC occurrence status, occurrence probability, evaluation accuracy, and evaluation period as accelerated test results.

[0062] [Table 2]

[0063] As can be seen from Table 2, in the examples of the present invention, the same SCC susceptibility as in the environment simulating an actual liquid ammonia tank could be evaluated within 720 hours. On the other hand, in the comparative examples, SCC did not occur in the steel material in which SCC had occurred in the environment simulating an actual liquid ammonia tank, and SCC susceptibility could not be evaluated. [Industrial Applicability]

[0064] According to the present invention, it is possible to provide an accelerated ammonia stress corrosion cracking test method capable of evaluating the ammonia stress corrosion cracking susceptibility of a metallic material with good accuracy and in a short period of time. Moreover, by using the test method of the present invention, it becomes possible to evaluate the ammonia stress corrosion cracking susceptibility of a metallic material with high accuracy and in a short period of time. The test method of the present invention is very useful for evaluating the ammonia stress corrosion cracking susceptibility of a metallic material, and can be advantageously used for the selection and development of metallic materials having excellent ammonia stress corrosion cracking resistance that can be suitably used for structures for transporting or storing liquid ammonia.

Claims

1. Metal test pieces to which external stress has been applied or which have residual stress are subjected to a gas partial pressure of 0.002 to 0.200 bar containing 0.01 mass% or more ammonium carbamate. 2 and polarizing the specimen to a corrosion potential of 0 to +1.0 V.

2. 2. The ammonia stress corrosion cracking accelerated test method according to claim 1, wherein the surface of the metal test piece immersed in the liquid ammonia is cathodically polarized and then polarized to 0 to +1.0 V with respect to a corrosion potential.

3. 3. The method for accelerated ammonia stress corrosion cracking testing according to claim 1, wherein the liquid ammonia is stirred during the test.

4. Metal test pieces to which external stress has been applied or which have residual stress are subjected to a gas partial pressure of 0.002 to 0.200 bar O. 2 1. A method for accelerated ammonia stress corrosion cracking testing, comprising: immersing a specimen in liquid ammonia containing

5. 5. The method for accelerated ammonia stress corrosion cracking testing according to claim 4, wherein the surface of the metal test piece immersed in the liquid ammonia is cathodically polarized.

6. 6. The method for accelerated ammonia stress corrosion cracking testing according to claim 4 or 5, wherein the liquid ammonia is stirred during the test.

Citation Information

Patent Citations

  • Method for evaluating resistance to corrosion of material under ammonium hydrosulfide environment

    JP2006266955A

  • Method for inhibiting adherence of radionuclide to carbon steel member of nuclear power plant

    JP2020098183A

  • Apparatus and method for treating volatile ammonia gas

    JP7128382B1

  • Corrosion resistant duplex steel alloy, objects made thereof, and method of making the alloy

    US20160325261A1

  • Circuit card having high density electric contact pads

    JP1985010575A